Motivação para o trabalho: um estudo com os profissionais de saúde das unidades básicas de saúde do município de Natal RN - Alves Filho, Antonio (2012)
This thesis studied the motivation to work among health professionals of the Basic Unities (BUH) in the health network of the city of Natal (RN). It was understood that the work motivation is a process. Then, the expectation theory was applied and motivation components (results of work, expectative, valence, instrumentality, and motivational force) were used to analyses. It s understanding the motivation as multifaceted phenomenon, the psycho sociological perspective was adopted. The research was developed in two phases: one with application of Work Motivation and Meaning Inventory (WMMI), and another with interview. In the first phases, the analysis of results revealed that the major factors contributing to increase the motivational force to health professionals in the BUH´s are: in valence, Self Expression and Personal Realization (VF2), Personal and Family Survival (VF3); in expectative, Self Expression and Work Justice (EF1), Safety and Dignity (EF2) and Responsibility (EF4); in instrumentality, Involvement (IF1) and Recognition and Economic Independence (IF4). In opposition, the factors that more contribute to reduce the motivational force are Wear and Dehumanization factors in valence (VF4), in expectative (EF3), and in instrumentality (IF4), behind the Work Justice Factor (IF2). Basing in content analysis of interviews, it was possible to associate by equivalence, the senses presented by health professionals with obtained results of first phase, indicating that the results of second phase corroborated and complemented those of first one. This possibility broadened the comprehension of the studied phenomenon. In speaking of the respondents, it was visible the presence of contents showing that they perceive the Health System and BUH´s in degradation. In the first phase, the participants´ instruction also predict the results in motivation, and in the interviews can be saw that the instruction is associated with the opportunities in outside of system. As work motivation is a process, the impact of personal and occupational characteristics tend to interact with contextual aspects. It was concluded the majority of health professionals present the moderated motivational force, but it was falling because they experience and perceive a degrading context with work condition increasingly unfavorable.